Utilization of Coconut Shell Waste Into Coconut Shell Charcoal to Improve The Welfare of The People of Togawa Village, South Galela District, North Halmahera Regency - Amran Eku; Adiyana Adam (Archipelago, 2020)
Coconut shell is a solid waste from processed coconut that has been taken coconut meat to get coconut milk. Coconut shells are generally used for fuel, household purposes or souvenirs. Togawa village, South Galela district, North Halmahera Regency is one of the villages producing coconut shells. To increase the economic value of the community, coconut shell can be processed into products that have a higher selling value. The abundance of coconut shells can be raised as the potential of the village in improving the economy of the community. The obstacle encountered to maximize coconut shell waste is the lack of skills of citizens in utilizing existing potentials. This community empowerment program aims to improve the welfare of the community. This implementation is designed using training methods with a system of delivery of material in theory or socialization and practice of the learning that has been done. Coconut shell charcoal can be used as a material for coconut shell charcoal and activated carbon. Activated carbon is a perpori material that has the ability to absorb the polluter contained in water that is as a water filter. The implementation of the program is carried out by socializing and applying it to the community. The results of community service in Togawa village can have a positive impact in developing independent businesses to improve the welfare of the surrounding community.Keywords: Coconut shell, coconut charcoal, activated carbon, Togawa Village